Serum mineral status during pregnancy in cows - Yildiz, Hamit; Kaygusuzoglu, Erdal; Aydin, Muhterem (The Indian Journal of Animal Sciences, 2011)
In this study, the serum concentrations ofcalcium (Ca), zinc (Zn), copper (Cu), iron (Fe), potassium (K) and sodium (Na) in 12 cows, 3-8 year old, during pregnancy and post-partum, and the relations among stich parameters were researched. Parallel variations of serum Cn and eu concentrations were noticed. They significantly increased from the tifth month, were maxima on the sixth month and thereafter they gradually declined until the parturition day. Zn concentrations were found modified (from the third 1110nth) and remained elevated throughout the pregnancy, with maximum values on the fourth and fifth months. fe, Na and K tended to decrease during pregnancy. From the third to the eighth month a significant decline of Fe was observed, and Kconcentration were particularly lower on the fifth and the seventh month. Na concentrations fluctuated, marked decrease ofNa were observed on the fourth month and on the ninth month and during postpartum. The important correlations were determined between Ca-Cu, Ca-Zn, Ca-Fc, Cu-Zn in various months of pregnancy and the clay of delivery. A significant relation was found between Fe-Zn during the pregnancy. Any change due to the delivery status was not determined in the levels ofCa, Cu, Zn, Fe, K and Na during the pregnancy and postparturition. In conclusion, it was agreed that the levels of serum Ca, Cll and Zn levels decreased as determllled during the last months of the pregnancy and postparturition.